Perancangan Sistem Penunjang Keputusan Penerimaan Siswa Baru Madrasah Aliyah (MA) Darussalam Manuju Kab. Gowa Menggunakan Algoritma Fuzzy Logic Berbasis Web - Abdul Wahid; Mustari Lamada; Titing Titing (Sakura Publisher, 2024)
This study will use fuzzy logic algorithm with mamdani model for new student selection using several criteria. Based on the survey that has been conducted on schools that conduct student selection, several criteria were obtained, including diploma grades, report card grades, and distance from home. The design of this decision support system aims to increase efficiency and objectivity in the process of admitting new students at Madrasah Aliyah (MA) Darussalam Manuju, Gowa Regency. The system built using the Fuzzy Logic algorithm allows the integration of various assessment parameters such as report card grades and diploma grades.The overall system testing results were carried out using several methods, namely the black box test method which obtained overall functional suitability. Keywords: Fuzzy Logic, New Student Admissions, Decision Support Systems